Extended capability models for Carbon Fiber Composite (CFC) panels in the Unstructured Transmission Line Modelling (UTLM) method - Meng, Xuesong; Vukovic, Ana; Benson, Trevor M.; Sewell, Phillip (Institute of Electrical and Electronics Engineers, 2016)
An effective model of single and multilayered thin panels, including those formed using carbon fiber composite (CFC) materials, is incorporated into the Transmission Line Modeling (TLM) method. The thin panel model is a one-dimensional (1D) one based on analytical expansions of cotangent and cosecant functions that are used to describe the admittance matrix in the frequency domain; these are then converted into the time domain by using digital filter theory and an inverse Z transform. The model, which is extended to allow for material anisotropy, is executed within 1D TLM codes. And, for the first time, the two-dimensional (2D) thin surface model is embedded in unstructured three-dimensional (3D) TLM codes. The approach is validated by using it to study some canonical structures with analytic solutions, and against results taken from the literature. It is then used to investigate shielding effectiveness of carbon fiber composite materials in a practical curved aerospace-related structure.